A construção de um direito fundamental à alimentação saudável e o desenvolvimento sustentável - Mattei , Silvia (2022)
The general objective of this thesis (which encompasses its theme) is again about healthy food as a right under construction, which is consolidated as an undeniable right, a right inherent to the human being, which is in line with the stage of intergenerational solidarity. Elements are presented that allow a systematic interpretation in the verification of this right and in mechanisms for its. In this sense, such consolidation is sustained in four specific objectives that will be addressed in each of the chapters of the development of the Thesis. The first objective is to recognise the importance of sustainable development for the fulfilment of the 2030 Agenda and recognize Rawls and Sen's idea of justice as a way to give opportunity to all, for the reduction of social inequalities, with a society built on a system of social cooperation between free and equal people, in a Sustainable Democratic State of Law, with provision in the Federal Constitution and international treaties and conventions. It also aims to analyze and understand fundamental rights and establish the constitutional basis of the right to healthy eating, beyond adequate food, as a fundamental right, related to human dignity, as well as the doctrinal references of its conceptualization. In this sense, for the construction of the right to healthy food, the production and consumption of agroecological foods should be promoted and the consumption of agroecological foods and understand what are the changes necessary for this to occur, from the choice of the transition from conventional to organic culture, as well as the education of society to increase the consumption of these products. In this way, the role of the State is crucial, as an instrument of incentive and viability, through effective public policies. Thus, the last objective proposes guidelines to municipalities, when the elaboration or reform of the Economic Development Plan, a specific axis related to sustainable and healthy eating, adaptable to the reality of each municipality or region, as well as to bond with previous objectives. The idea is that sustainable initiatives start from the grassroots, in municipalities, by proximity to people, but we must also think of a great national and global ecological pact, so that, in fact, healthy food can be realized as a fundamental right for everyone. For the elaboration of this thesis, the hermeneutic (Hans-Georg Gadamer) and complex (Edgar Morin) methods were used.